A mitogenome sequence of an Equus hydruntinus specimen from Late Quaternary site of San Teodoro Cave (Sicily, Italy). (15th May 2020) - Catalano, Giulio; Modi, Alessandra; Mangano, Gabriella; Sineo, Luca; Lari, Martina; Bonfiglio, Laura
Abstract: Equus hydruntinus was a small equid that ranged from the Iberian Peninsula to Middle East. In Italy it has been considered present from the Middle Pleistocene to its extinction in the Middle-Late Holocene. E. hydruntinus shares plesiomorphic traits with other known Pleistocene equids. As a consequence, its classification has always been problematic. Genetic analyses on few fossil remains from Iran and Crimea have revealed that E. hydruntinus was more closely related to extant hemiones. To further investigate its systematic position, using target-enrichment capture and next-generation sequencing, we reconstructed a near complete mitogenome of a specimen from San Teodoro Cave from Sicily radiocarbon dated at 23-21 ka cal. BP. Comparisons with extant and extinct equids demonstrate close relationship between this specimen and the Asian wild asses, supporting previous genetic and morphological studies. Furthermore, our findings confirm the occurrence of E. hydruntinus species in Sicily, that presumably might have represented a typical glacial refugium during the LGM. Highlights: First complete mtDNA genome obtained from a Late Quaternary specimen of E. hydruntinus from Southern Mediterranean. Sicilian specimen shows a substantial affinity with Asiatic wild asses, supporting previous genetic and morphological studies.